Осип-Роман Сорохтей та стрілецькі часописи - Макойда, О. (Інститут народознавства НАН України, 2007)
The article treats the subject of the artist Osyp Sorokhtey’s contribution to editorial offices of satirical magazines during World War I. In the study, special attention is being paid to the period of O.Sorokhtey’s service in the ranks of Ukrainian Sich Riflemen military formations. This period had quite a positive influence upon the artist’s further creativity.